2023
DOI: 10.1093/ptj/pzad021
|View full text |Cite
|
Sign up to set email alerts
|

Six Externally Validated Prognostic Models Have Potential Clinical Value to Predict Patient Health Outcomes in the Rehabilitation of Musculoskeletal Conditions: A Systematic Review

Abstract: Objective The purpose of this systematic review was to identify and appraise externally validated prognostic models to predict a patient’s health outcomes relevant to physical rehabilitation of musculoskeletal conditions. Methods We systematically reviewed 8 databases and reported our findings according to PRISMA 2020. An information specialist designed a search strategy to identify externally validated prognostic models for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The preliminary version of the MAPS questionnaire was developed based on a recent pilot study conducted by the research team that required the combination of sociodemographic characteristics, clinical data and outcome measures with prognostic value (Longtin et al., 2021; Naye et al., 2022). A literature search was performed through systematic review by our research team as a preliminary step toward the development of the questionnaire (Naye et al., 2023; Tousignant‐Laflamme et al., 2023). From these results, validated prognostic tools for musculoskeletal rehabilitation and PF of musculoskeletal disorders were extracted to determine the preliminary content items of the MAPS questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary version of the MAPS questionnaire was developed based on a recent pilot study conducted by the research team that required the combination of sociodemographic characteristics, clinical data and outcome measures with prognostic value (Longtin et al., 2021; Naye et al., 2022). A literature search was performed through systematic review by our research team as a preliminary step toward the development of the questionnaire (Naye et al., 2023; Tousignant‐Laflamme et al., 2023). From these results, validated prognostic tools for musculoskeletal rehabilitation and PF of musculoskeletal disorders were extracted to determine the preliminary content items of the MAPS questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent systematic review concluded that validated prognostic models are available to help manage musculoskeletal disorders (Naye et al., 2023). Moreover, there are overviews of systematic reviews that clearly identify potential PF pertaining to musculoskeletal disorders (Nieminen et al., 2021; Otero‐Ketterer et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its limitations, SBT has important clinical benefits. In a comprehensive systematic review, Naye et al [33] ranked it as one of six potentially clinically useful prognostic models for patients with musculoskeletal disorders whose external validity was investigated.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…duration of symptoms, pain intensity) (Artus, Campbell, Mallen, Dunn, & van der Windt, 2017;Beattie & Nelson, 2007;Bruls, Bastiaenen, & de Bie, 2015;Martin et al, 2000) and work-related disorders (Tousignant-Laflamme et al, 2023) have been identified. A recent review identified six externally validated prognostic models that predicted health outcomes relevant to the physical rehabilitation of general musculoskeletal conditions (Naye et al, 2023). The review expressed concern that using these models can be complex, especially when determining the suitability of a given model for their practice environment (Naye et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review identified six externally validated prognostic models that predicted health outcomes relevant to the physical rehabilitation of general musculoskeletal conditions (Naye et al., 2023). The review expressed concern that using these models can be complex, especially when determining the suitability of a given model for their practice environment (Naye et al., 2023). These limitations, and the time required to complete the prognostic tools are likely why they have not been routinely adopted into clinical practice.…”
Section: Introductionmentioning
confidence: 99%